An Evaluation of Changes to the Turkish High School Physics Curriculum - Çepni̇, Sali̇h; Kurnaz, Mehmet Altan (Canadian Center of Science and Education, 2012)
A New Turkish Physics Curriculum has been constructed between the years 2006-2009. It is to the gaining of new perspectives. The purpose of this paper, therefore, is to reflect on the nature of the New Turkish Physics Curriculum (NTPC). To this end, the authors focus on the five themes of the NTPC using a document analysis method: basic reasons and needs of the NTPC, fundamental approaches of the NTPC, learning areas of the NTPC, characteristics of teaching activities in terms of the NTPC, needs of the NTPC. This paper highlights thus focusses on the fundamentals of the NTPC and considerations of its easy adaptation into practice.
Keywords: 4. Education; 11. Sustainability; 10. No inequality; 7. Clean energy